A Relational Approach Towards Decolonizing Curriculum Development within the Colonial Postsecondary Institution - Daley, Andrea; Neufeld, Hannah; Skinner, Kelly; Van Katwyk, Trish; Smoke, Mary Lou; Smoke, Dan; Antone, Kaluyahawi (Jocelyn) (Engaged Scholar Journal, 2024)
The Canadian academy is dominated by Western epistemologies that devalue Indigenous ways of knowing and marginalize Indigenous communities, cultures, and histories (Louie et al., 2017). This paper draws on a cross-disciplinary, interprofessional collaboration between a School of Public Health Sciences and School of Social Work to develop an online graduate course that sought to advance knowledge and practice in Indigenous wellbeing and health through a social justice lens. We explore key considerations, strategies, and challenges undertaken by an interdisciplinary group of non-Indigenous professors to create a learning experience for students that challenges colonial ways of seeing, being, knowing, and doing in the professional practice fields of public health and social work and that serves to elevate and sustain Indigenous voices, knowledges, sciences, and practices within the academy. In doing so, we centre the process of course development, including working with an Indigenous Advisory Circle and Indigenous contributors of content, guest lecture videos, and artwork. The paper describes the creation of a relational teaching and learning community, while raising concerns about the institutionalization of this approach to Indigenous-focused course development in the absence of the structural changes needed to enhance the presence of Indigenous faculty and Elders in academic institutions.